2005
DOI: 10.2528/pier04100502
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Simulation of Reflected Em Pulses From Objects Vibrating at Different Frequencies

Abstract: Abstract-In this report one-dimensional simulation of Electromagnetic pulses reflected from moving and/or vibrating perfectly conducting surfaces is presented. The computational results are obtained through the application of the method of characteristics with the aid of the characteristic variable and the relativistic boundary conditions. The reflecting perfect surface is set to constantly travel at relatively high speed and/or sinusoidally vibrate with very high frequency in order to easily observe the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Many studies providing theoretical solutions and computational results for problems involved with moving or oscillating objects [1][2][3][4][5][6][7][8][9][10][11][12][13] or rotating objects [14,15] can be easily found. Harfoush et al adapted the finite-difference time-domain (FDTD) technique for simulating electromagnetic wave scattering from moving surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies providing theoretical solutions and computational results for problems involved with moving or oscillating objects [1][2][3][4][5][6][7][8][9][10][11][12][13] or rotating objects [14,15] can be easily found. Harfoush et al adapted the finite-difference time-domain (FDTD) technique for simulating electromagnetic wave scattering from moving surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For the same objective, under the excitation of a Gaussian electromagnetic pulse or continuous wave train, the method of characteristics (MOC) combined with the relativistic electromagnetic field boundary conditions and successfully predicted the reflected electromagnetic fields from perfect planes moving at a constant velocity and/or vibrating at a fixed frequency. The computational results revealed not only the Doppler frequency shift but also the changes in phase and amplitude [1][2][3]. Though so, attempts to numerically simulate the electromagnetic scattering problem from rotating objects are postponed for the reason that grid cells suffer from being stretched and distorted due to the rotational motion of the object under examination, which brings the numerical efforts a major difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years much attention has also been given to scattering from deterministic surfaces undergoing translation, rotation and vibration. For example, one-dimensional deterministic scattering from vibrating planes [4,5] and rotating cylinders [6] has been treated by applying relativistic boundary conditions and the method of characteristics to obtain numerical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies investigating this issue. Some studies focus on the derivation of the theoretical solutions for the EM scattering by perfect conductors in uniform translational motion [1][2][3][4][5][6][7][8][9][10][11], some on the EM scattering by linearly vibrating objects [12][13][14], some on the simulation of the scattered EM fields from perfect planes moving and vibrating [15][16][17], and one on a moving dielectric half-space [18]. Among them, Harfoush et al provided computational results, in addition to the theoretical analysis, by using the finite-difference time-domain (FDTD) technique, in which both Faraday's and Ampere's laws were employed as aides to respectively approximate the magnetic and electric fields immediately next to the moving surface whenever the surface travels away from the grid point [3].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations of the reflected EM fields from uniformly travelling and oscillating perfect plane were carried out using MOC in collaboration with the relativistic EM field boundary conditions, and the computational results revealed that the reflected fields disclose not only the modulations in phase and amplitude but also the Doppler shift in spectrum. It is also explained that, due to the movement of the boundary, some moments grid cells were gradually eliminated from the grid system, and for other certain moments, grid cells were introduced little by little into the grid system [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%